Determination of cephalosporin antibiotic residues in milk using liquid chromatography – tandem mass spectrometry (LC – MS/MS) method - Alija, Gjulai; Hajrulai musliu, Zehra; Uzunov, Risto; Ahmeti Lika, Sihana; Havziu, Drita (University of Tetova, 2022)
The possible presence of cephalosporin residues in milk is one of the key issues for food safety which arouses great public concern. When these classes of drugs are retained in food stuff, this may result in allergic or toxic reactions, alterations in the intestinal flora, bacterial resistance and the inhibition of fermentation in the dairy industry. A modest liquid chromatographytandem mass spectrometry (LC-MS/MS) method was developed and validated for the simultaneous determination of 3 cephalosporins residues (cephapirin, cefalexin, ceftiofur) in milk. The method was validated in accordance with the criteria defined in Commission Decision 2002/657/EC. Samples are initially extracted with EDTA-Mcllvain buffer and after that solid-phase extraction clean-up with Oasis HLB cartridge was performed. Chromatographic separation was achieved using a C18 column. From the gained results from the validation study, it can be concluded that the method was linear with coefficient of correlation (R2) from 0.9812 to 0.9896. Detection capabilities (CCβ) ranged between 10.27 and 11.97 μg/L and decision limits (CCα) ranged between 9.59 and 12.39 μg/L. The recovery values ranged from 84.53 to 95.70 % with relative standard deviations (RSD) no larger than 17.25 %. This validation study provided evidence that the method it’s suitable to be applied in routine analysis for the detection of cephalosporin residues in milk.
Keywords: cephalosporin residues, milk, validation, LC-MS/MS method